INNOVATIONS IN THE EUROPEAN RAILWAY INDUSTRY FOR THE NEXT TWENTY YEARS - Knižka, Ján; Klapita, Vladimír (Doprava a spoje, 2005)
The paper deals about innovations in the European Railway industry for future time twenty years as far as ensure connectivity of the networks in Europe with regard on the integration of the traffic flows, relationship on the capacity of railway lines and stations, environment and safety of rail transport.